Assistência estudantil: um estudo multicaso sobre suas condicionalidades e ações de prevenção a retenção e evasão em universidades multicampi - Schuch, Marta Cristina (2024)
Access to and retention in higher education in Brazil has historically occurred unequally, with the implementation of public policies for expansion, inclusion and retention representing an important advance for society and an opportunity to reduce inequality in access to education. In this sense, the creation of the National Student Assistance Program - PNAES regulated by Decree nº 7,234, of July 19, 2010, executed within the scope of the Ministry of Education, aims to expand the conditions of permanence in federal public higher education. The aforementioned Decree defines that priority will be served within the scope of the PNAES, students from the public basic education network or with a per capita family income of up to one and a half minimum wages and establishes that it will be up to the institutions to define the criteria and methodology for selecting students. undergraduate students to benefit. Based on this context, the objective of this research was to analyze how monitoring and evaluation actions contribute to the prevention of dropout and retention of undergraduate students included in student assistance (AE) policies at three federal public universities, in the interior of Southern region of Brazil, with a multicampi structure (Federal University of Santa Maria - UFSM, Federal University of Fronteira Sul - UFFS and Federal University of Pampa - UNIPAMPA) and the actions developed regarding non-compliance with the counterparts regulated by the institutions and prevention actions to evasion and retention. This study, of a qualitative, exploratory and comparative nature, was developed through documentary research, and semi-structured interviews with student assistance managers, and Education Administrative Technicians (TAEs) who work with the conditionalities (criteria or counterparts) for staying in the said policies. Thus, 34 (thirty-four) interviews were carried out, from October 24, 2022 to December 20, 2022. Data analysis was carried out based on the interviewees' responses using content analysis. With this work, it was possible to map the conditions for remaining in student assistance, as well as actions to prevent retention and dropout at the different universities researched. From the results, it is possible to observe that the development of preventive evasion and retention actions is precarious or almost non-existent, mainly due to the lack of evaluation and monitoring mechanisms for students included in student assistance during the semester, as well as a database with information related to dropout and retention that can support the planning of these actions, which in some situations makes the management of student assistance difficult.